2005
DOI: 10.1080/09687860500287832
|View full text |Cite
|
Sign up to set email alerts
|

Binding of antibiotic amphotericin B to lipid membranes: monomolecular layer technique and linear dichroism-FTIR studies

Abstract: Amphotericin B (AmB) is one of the main antibiotics applied in treatment of deep-seated mycotic infections. Tensiometric technique has been applied to monitor binding of AmB, from the water subphase, to the lipid monomolecular layers, formed with dipalmitoylphosphatidylcholine at the air-water interface. Time dependencies of surface pressure in the monolayers demonstrate strong enhancement of AmB binding to monolayers brought about by sterols present in the membranes. The monolayers have been deposited to a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
2
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 22 publications
4
53
2
1
Order By: Relevance
“…Such a protocol yields efficient binding of AmB to the lipid membranes as described in our previous work [13]. the systems studied is highly heterogeneous.…”
Section: Accepted M Manuscriptmentioning
confidence: 96%
See 4 more Smart Citations
“…Such a protocol yields efficient binding of AmB to the lipid membranes as described in our previous work [13]. the systems studied is highly heterogeneous.…”
Section: Accepted M Manuscriptmentioning
confidence: 96%
“…It has been also proposed that selectivity toward cells of fungi is based upon a difference of the radii of porous structures of AmB binding ergosterol and cholesterol [6,9]. On the other hand, very recent reports show that alternatively both the biological action of the drug as well as toxic side effects may be directly related to the effect of AmB on physical properties of the membranes [10][11][12][13]. The 1 H-NMR technique studies demonstrated that the polar headgroup region of the membranes, rather than the hydrophobic core, is a predominant site of binding of AmB from the water phase [12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations